1983
DOI: 10.7164/antibiotics.36.1312
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies on lipiarmycin I. Characterization by 1H and 13C NMR spectroscopy and isolation of methyl 2-O-methyl-4-O-homodichloroorsellinate-.BETA.-rhamnoside.

Abstract: 1H and 13C NMR spectral studies of lipiarmycin in CDCI , and in pyridine-d; provided evidence for the six partial structures I-VI and the two sugar units 1 and 2. Acid methanolysis led to the isolation of methyl 2-O-methyl-4-O-homodichloroorsellinate-,3-rhamnoside, whose structure was determined by spectroscopic methods.Lipiarmycinl.2) is a chlorine containing antibiotic produced by Actinoplanes deccanensis ATCC 21983, active mainly against Gram-positive bacteria. While the weak in vivo activity delayed furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…3:1 mixture of two closely related macrolides, lipiarmycin A3 and lipiarmycin A4, whose gross chemical structures were determined in 1987. [5] The complete relative and absolute configuration of 1 (from Dactylosporangium aurantiacum) was elucidated in 2005 by X-ray crystallographic analysis; [6] importantly, most recently, 1 has been shown to be identical to lipiarmycin A3. [7] The structure of tiacumicin B (1) features an 18-membered macrolactone core with four chiral centers and a high degree of unsaturation; an additional, hydroxy-bearing ste-reogenic center is present in the short side chain attached to C17.…”
Section: Florian Glaus and Karl-heinz Altmann*mentioning
confidence: 99%
“…3:1 mixture of two closely related macrolides, lipiarmycin A3 and lipiarmycin A4, whose gross chemical structures were determined in 1987. [5] The complete relative and absolute configuration of 1 (from Dactylosporangium aurantiacum) was elucidated in 2005 by X-ray crystallographic analysis; [6] importantly, most recently, 1 has been shown to be identical to lipiarmycin A3. [7] The structure of tiacumicin B (1) features an 18-membered macrolactone core with four chiral centers and a high degree of unsaturation; an additional, hydroxy-bearing ste-reogenic center is present in the short side chain attached to C17.…”
Section: Florian Glaus and Karl-heinz Altmann*mentioning
confidence: 99%
“…The producer strain was isolated on February 29th, 1972 – in a leap year – and accordingly, the produced compounds were named lipiarmycins. Preliminary structural studies on lipiarmycin identified the rhamnoside‐dichlorohomoorsellinate moiety as well as the modified noviose as important structural features ( Figure ) . However, lipiarmycin was later reported to actually be composed of two compounds, lipiarmycin A3 ( 1 ) and A4 ( 9 ), whose structures were finally elucidated after extensive NMR and degradation studies .…”
Section: Isolation Structure Elucidation and Biological Activitymentioning
confidence: 99%
“…Although its chemical–physical properties, its biological activity [2,3], and its NMR characterization [4] were thoroughly described within a few years, this material was only recognized to be a mixture of two related products in 1987, when the first comprehensive study [5] on the chemical structure determination of lipiarmycin was published. Based on chemical degradations and NMR studies, the two antibiotics extracted from Actinoplanes deccanensis —named lipiarmycin A3 ( 1 ) and lipiarmycin A4 ( 2 )—proved to be characterized by a common 18-membered macrolactone attached to two glycosyl moieties, namely 2- O -methyl-4- O -homodichloro-orsellinate-β- d -rhamnose and 4- O -isobutyrate-5-methyl-β-rhamnose.…”
Section: Introductionmentioning
confidence: 99%